Understanding the impact of culture as a destination image attribute on sustainable tourism - Zhou, Zijun; Siow, May Ling; Mohd Ariffin, Noor Fazamimah; Abdul Aziz, Faziawati (Secholian Publication, 2024)
This study aims to underscore the pivotal role of cultural attributes in shaping destination image and examines their implications for sustainable tourism. Through a comprehensive review of relevant literature, the study proposes a conceptual framework to delve into the multifaceted effects of cultural attributes on destination image formation and offers strategies and guidelines for fostering sustainable tourism practices. The findings of the study underscore the significance of cultural attributes in bolstering the competitiveness of destination images in sustainable tourism, while also analyzing their interconnectedness across social, economic, and environmental dimensions. The societal impact of this study lies in highlighting the pivotal role of cultural attributes in shaping perceptions and allure associated with destination images, thereby furnishing a vital reference point for crafting and executing a targeted research agenda in urban tourism. Ultimately, this study furnishes a valuable theoretical framework and perspective conducive to the advancement of sustainable tourism endeavors.